Quantifying the relationship and contribution of mitochondrial respiration to systemic exercise limitation in heart failure. (20th February 2021) - Knuiman, Pim; Straw, Sam; Gierula, John; Koshy, Aaron; Roberts, Lee D.; Witte, Klaus K.; Ferguson, Carrie; Bowen, Thomas Scott
Abstract: Aims: Heart failure with reduced ejection fraction (HFrEF) induces skeletal muscle mitochondrial abnormalities that contribute to exercise limitation; however, specific mitochondrial therapeutic targets remain poorly established. This study quantified the relationship and contribution of distinct mitochondrial respiratory states to prognostic whole‐body measures of exercise limitation in HFrEF. Methods and results: Male patients with HFrEF ( n = 22) were prospectively enrolled and underwent ramp‐incremental cycle ergometry cardiopulmonary exercise testing to determine exercise variables including peak pulmonary oxygen uptake (V̇O2peak ), lactate threshold (V̇O2LT ), the ventilatory equivalent for carbon dioxide (V̇E /V̇CO2LT ), peak circulatory power (CircPpeak ), and peak oxygen pulse. Pectoralis major was biopsied for assessment of in situ mitochondrial respiration. All mitochondrial states including complexes I, II, and IV and electron transport system (ETS) capacity correlated with V̇O2peak ( r = 0.40–0.64; P < 0.05), V̇O2LT ( r = 0.52–0.72; P < 0.05), and CircPpeak ( r = 0.42–0.60; P < 0.05). Multiple regression analysis revealed that combining age, haemoglobin, and left ventricular ejection fraction with ETS capacity could explain 52% of the variability in V̇O2peak and 80% of the variability in V̇O2LT, respectively, with ETS capacity ( P = 0.04) and complex I ( P = 0.01) the only significant contributors in the model. Conclusions: Mitochondrial respiratory states from skeletal muscle biopsies of patients with HFrEF were independently correlated to established non‐invasive prognostic cycle ergometry cardiopulmonary exercise testing indices including V̇O2peak, V̇O2LT, and CircPpeak . When combined with baseline patient characteristics, over 50% of the variability in V̇O2peak could be explained by the mitochondrial ETS capacity. These data provide optimized mitochondrial targets that may attenuate exercise limitations in HFrEF.